A geographical analysis of thunderstorm in southern Bangladesh - Mohiuddin, Md.; Nowreen, Samshad; Uddin, Md. Forhad; Hossain, Malik Akram (National Geographical Journal of India, 2021)
Thunderstorms are one of the extreme devastating natural disasters, which cause death, injuries and adverse loss in agriculture, housing structure and domestic animals during the period of pre-monsoon and monsoon. Bangladesh is vulnerable to thunderstorm disasters due to its location and weather conditions. Rural people are severely affected by a thunderstorm. For this research, necessary data were collected from secondary as well as primary sources. Thunderstorm related information was randomly gathered from the 150 affected family members, and close relatives. The study demonstrates that the working people especially farmers and school going students were severely affected. The research also identies three impacts of thunderstorms on humans, types of damage and monetary loss. In terms of thunderstorm induced casualty, the number of death was higher than other casualties in the study area. This research also revealed that above 67 % of people succumbed to death by thunderstorm which damaged crops, households, animals and trees. People in the study area also suffered from physical damage, for example, injuries to ears, eyes, and body. More than 37% of people faced hearing problems due to strikes of the thunderstorm. The study also identies the risk factors responsible for the thunderstorm, such as lack of knowledge about a thunderstorm, outdoor activities, diurnal, and locational variation. Policymakers and planners will nd insights from this research to mitigate the impact of thunderstorm disasters in rural Bangladesh.